Gerenciamento de estoques por meio da classificação ABC: estudo em uma empresa supermercadista de pequeno porte no processo de profissionalização - Ribeiro, Adriana Nobre da Silva (2022)
Companies are, increasingly, with the need to seek improvements that maximize their gains as well as minimize losses. Thus, small businesses have undergone transformations over the years, no longer being a family space, with loyal customers, to enter the world of competitiveness and the best space and price. This work aims to identify the advantages for inventory management in the professionalization process, from the use of the ABC classification, in a small supermarket retail company located in Fortaleza - CE. From the classification, it is intended to identify the level of importance in the sales volume, the products that bring the greatest return for each family and which product families generate greater profitability for the business. From this perspective, this study intends to verify the professionalization process based on the ABC classification in Mercadinho's inventory management and to suggest improvement proposals for small companies that intend to become professional in this area. Due to these specificities, this work is characterized as a Case Study, with an applied research classification, of a descriptive nature, as it involves standardized and structured techniques for data collection. After the analysis, it was possible to observe that the line that contributed the most to the company's average revenue are the products classified in category A of the cereal family. As for the professionalization process. It was concluded that there is evidence of that the management of small businesses is moving towards professionalization, because it is using technology systems aimed at stock control, but it needs to invest in employee training or in hiring a professional with managerial skills to organize the business, management of stock needs to improve its organizational structure, as there is a lack of planning, strategies and formal actions, so that decisions are centered on the owners and taken in the light of action-reaction.